South African men and women living with HIV have similar distributions of pain sites - Antonia L. Wadley; Romy Parker; Vanessa A. Mukhuba; Andani Ratshinanga; Zipho Zwane; Peter R. Kamerman (AOSIS, 2022)
Background: No studies have investigated sex differences in the location and number of pain sites in people living with human immunodeficiency virus (HIV) (PLWH), despite evidence that women, in general, bear a greater burden of pain than men. Aim: To determine sex differences in the location and number of pain sites, and whether there were demographic or disease-related differences in the number of pain sites. Setting: South African tertiary hospital HIV clinics and a community healthcare centre Methods: We conducted a retrospective analysis of records from South African PLWH who had pain. Results: Of the 596 participant records, 19% were male (115/596) and the median number of pain sites for both sexes was 2 (interquartile range [IQR]: 1 to 3). Pain was most frequently experienced in the head (men: 12%, women: 38%), feet and ankles (men: 42%, women: 28%), abdomen (men = 19%, women = 28%) and chest (men = 20%, women = 20%). After correcting for multiple comparisons, males were less likely to experience headache than females (Fisher's exact text, odds ratio [OR] = 0.23, 95% confidence interval [CI]: 0.12 - 0.42, p = 0.000). Pain at other body sites was experienced similarly between the sexes. There was no meaningful variation in the number of pain sites between the sexes (logistic regression, p = 0.157). Conclusion: A similar location and number of pain sites were experienced by male and female South African PLWH. The locations of pain sites were different from previous reports, however, suggesting that research into pain in PLWH cannot necessarily be generalised across cultures.